2021
DOI: 10.3390/ijerph18084304
|View full text |Cite
|
Sign up to set email alerts
|

Snapshot of the Use of Urban Green Spaces in Mexico City during the COVID-19 Pandemic: A Qualitative Study

Abstract: The present qualitative research explores the factors that have influenced the use of urban green spaces (UGS) in Mexico City during the COVID-19 pandemic and the implications of their usage on residents’ well-being. This study was conducted using a combination of solicited audio and written diaries, photography, and in-depth interviews with 16 participants, aged 22 to 58. The article provides a critical reflection on the incentives and deterrents to the UGS use of participants while social distancing measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 71 publications
2
36
0
Order By: Relevance
“…The underlying mechanisms for these differences remain to be investigated and are essential for the planning of nature-based solutions and interventions when aiming to contribute to the sustainable development goals (Faivre et al, 2017;Maes & Jacobs, 2017;UN, 2015). For instance, in a qualitative study, women indicated that fear of violence hinders positive well-being experiences when visiting an urban park in Mexico during COVID-19 (Huerta & Cafagna, 2021). The issue of different mechanisms for different populations in the nature-health relationship has been summarized in a review by Masterton et al (2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanisms for these differences remain to be investigated and are essential for the planning of nature-based solutions and interventions when aiming to contribute to the sustainable development goals (Faivre et al, 2017;Maes & Jacobs, 2017;UN, 2015). For instance, in a qualitative study, women indicated that fear of violence hinders positive well-being experiences when visiting an urban park in Mexico during COVID-19 (Huerta & Cafagna, 2021). The issue of different mechanisms for different populations in the nature-health relationship has been summarized in a review by Masterton et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, heterogeneity has not only been investigated regarding population characteristics, but also with regards to nature characteristics, e.g., between different park types (Cheng et al, 2021;, as well as nature quality, in the studies of this review operationalized as higher greenness and vegetation (Cheng et al, 2021;Huerta & Cafagna, 2021). The few studies investigating heterogeneity and disparities regarding nature types in relation to mental health mirror a research gap that researchers has been identified prior to COVID-19 (Bratman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, urban planners, policymakers, and researchers have sought to determine which measures or policies can help maintain or improve overall health and build resilience amidst the public health crisis ( Chwaszcz et al, 2020 , Zhang and Ma, 2020 ). One activity that has had positive effects on residents’ general well-being during the novel coronavirus outbreak is the use of urban green spaces (UGS) ( Mayen Huerta and Cafagna, 2021 , Pouso et al, 2021 ). Given the restrictions on the use of indoor recreational spaces, UGS became especially important during lockdown periods because they allowed residents to perform physical activities, enjoy natural landscapes, and relax while socially distancing, thus making them a highly effective public health tool ( Geary et al, 2021 , Luo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous reasons for the negative impact of lockdowns on physical and mental health; some key reasons include (but are not limited to) increased sedentary lifestyle, physical inactivity, infection fears, financial loss, inadequate information, feeling of loneliness and boredom (Brooks et al, 2020;Peçanha et al, 2020;Ledford et al, 2021). In contrast, nature exposure including contact with blue and green spaces, indoor plants, gardening have the potential to mitigate against or buffer the negative health consequences with the potential for little/no negative impacts (Pouso et al, 2021;Mayen Huerta and Cafagna, 2021;Yang et al, 2021;Ribeiro et al, 2021).…”
Section: Introductionmentioning
confidence: 99%